(3eLehY GdEeGes - (3Rjf Hf Ydj Hf GdMSjf Hf Ydj Hf CHj WGdH,J (B122 (3g` s ((3aGWeI HfJ jhSa Hf jMji Hf CMeO RHGQI s)
(3ChdgG (B:s
(3cJGH GdWgGQI bGd (B: (3CNHQfG GdSjO GdCLd HOQ GdOjf YGeQ Hf RjO GdYdhi MOKfi CHh NGdO YeQh Hf NGdO GdhGSWi , bGd MOKfi RjO Hf Ydi Yf CHjg Yf CHjg Ydi Hf CHj WGdH Ydjge GdSdGe s
(3BNQgG (B:s
(3BNQg ai Uag QShd Gddg Udi Gddg Ydjg h Sde (B:" (3YQbg CWjH ef QjM GdeSc , de CQ bHdg hdG HYOg eKdg , Udi Gddg Ydjg hBdg hSde Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B80s
(3GdfSNI HgG MhGTs
(3Ydi JedcGJ ai GdbQf GdKGdK YTQs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCMbGa eLehYI Bd jMi (B(123) s
Keywords: (3abg GdePGgH GdCNQis